PERANCANGAN APLIKASI PENJUALAN PADA PT.BERLIAN KOMPUTINDO UTAMA BERBASIS WEB - Ardy Wijaya (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Web-based sales information system are system in the form of a website that can be accessed through the internet. This web site can be accessed through any computer device that connects to the internet around the world. So everyone can see this website. This website can also be accessed 24 hours a day. To simplify management of sales systems and promote the notebook etc. sales as well as increase sales and competitiveness, as well as simplyfy a ". This new system already can be used for online sales transactions. The used method is the SDLC (System Development Life Cycle) and Protoyping Keywords Web-based sales information system, SDLC (System Development Life Cycle), Prototyping